Competitiveness through Increased Added Value:: A Challenge for Developing Countries - Lind, Per (Journal of Comparative International Management)

(untitled) (Management Futures, 2005)
Abstracts A rising standard of living is the result of many contributing factors interacting in a complex pattern. One such contributing factor is the capacity of a nation's firms to achieve high levels of productiv ity, and to increase productivity over time. Small and Medium Enterprises (SMEs) in developing countries have significantly lower productivity, as measured by added value per employee in comparison with developed countries. One reason for this imbalance is the traditional business practice in many developing countries of price competition as opposed to product innovation and superior customer value. The concept of added value is used to characterise three business strategies with decreasing, unchanged and increasing added value. In the third strategy the increased added value is the result of a price increase, justified through improved functional product or service quality. Since product improvement mostly leads to higher costs, the crucial issue is to find a method to analyse when increased sales price, and hence also increase in added value, leads to lower profit due to higher production costs. The model suggested to cope with this issue is based on three parameters: added value grade, profit margin and refinement cost grade.